IMPLEMENTASI LEARNING MANAGEMENT SYSTEM MELALUI MODEL PROJECT BASED LEARNING - Wahyu Setiawan; Tatang Herman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The implementation of a learning management system (LMS) through the project-based learning (PBL) model is one of the alternatives that can be considered to improvstudent’ss learning outcomes and abilities. This study aims to examine the impact of LMS implementation through the PBL model on students' learning outcomes and abilities. The research method used was a case study with 30 IKIP Siliwangi and Widya Mandiri University students. Data were collected using observation, interview, and questionnaire instruments. Data analysis was carried out using a quantitative descriptive technique. The results showed that LMS implementation through the PBL model can improve students' learning outcomes, indicated by the increase in the percentage of students who received an A grade. In addition, LMS implementation through the PBL model can also improve students' critical thinking, teamwork, and communication skills. LMS implementation through the PBL model can also improve students' ability to manage their learning time, find and utilize information, adapt to changing learning environments, and manage emotions and stress.